Implementation of Socialization on Prevention of Non-Procedural Indonesian Migrant Workers - Hanif Shofarudin; Andry Indradi (Polteknik Imigrasi, 2020)
The objective of the Socialization of the Prevention of Non-Procedural Indonesian Migrant Workers (PMI-NP) is a preventive effort in the law enforcement process carried out by the Immigration agency through the activities of the Immigration Polytechnic cadets to reduce the number of Indonesian Non-procedural Migrant Workers in Indonesia. Preventive efforts are carried out in coordination with the Manpower Office in Pati District.The socialization of the prevention of Non-Procedural Indonesian Migrant Workers is carried out at the Indonesian Educational and Professional Development Institutions. The results of the implementation of these activities are expected that the public will have legal awareness of the process of becoming PMI procedurally, know the impact of the dangers of becoming PMI - NP, and provide legal certainty for PMI candidates so that they can become procedural PMIs so that it is safe to do work outside the territory of the Republic of Indonesia.